The Resilient Well-Being: A "Fantastic Binomial" In Working-Groups of Educational and School Services (Global Journal of Human-Social Science, 2021)
The aim of this study was to detect, monitor and promote subjective and collective "resilient well-being" in working groups of 16 different educational and school services, involving 190 educators and teachers. The methodology used was of the Research-Action kind, with the direct participation of the subjects in all phases of the research. According to authoritative theoretical models, a survey questionnaire was constructed to detect the perception of resilience and well-being, referred to both the professional self and its group of work. The analysis of the results shows a tendentially high attribution to the values assigned to the characteristics of resilient personality, to the condition of well-being in one's professional context and to the most acted out resilient behaviors -and ideally considered more effective -in response to a critical situation. However, the "humor" factor, as a "relaxing" pedagogical device of relational ties, should be strengthened. Well-being and resilience are thus constituted as paradigmatic pedagogical categories, of a self-eco-organizational nature, the formative value of which is in their dynamic nature of research of new regenerative balances -from ruptures, transformations and renewalsto be constantly restructured.
Keywords: well-being; resilience; working-groups; educational and school services; teachers’ training